Multimedia Journalism in Legal Education System - O. V. Tretyakova (Научный диалог)
This study explores the multimedia tools of legal journalism, which play a crucial role in the legal education system. The research is grounded in the concept of multimedia as a medium that integrates various forms of visual information, including photographs, illustrations, infographics, videos, animations, and more. The novelty of this research lies in its examination of the forms, purposes, and effectiveness of multimedia content within legal journalism. The objective of the study is to identify the use of multimedia tools in the content produced by Russian online media outlets on legal topics. The materials for this research include websites and special projects from Russian publications, analyzed from the perspective of visualization and multimedia integration, as well as the results of a media consumption survey. The author concludes that a limited range of multimedia elements — such as photographs, hyperlinks, and infographics—are utilized in publications addressing legal issues. In educational special projects, media outlets actively employ videos, interactive infographics, quizzes, and tests that could also be used to promote legal knowledge; however, multimedia projects on legal topics are rarely found in the Russian media landscape. The survey results further indicate that it is premature to assert a significant contribution of multimedia journalism to legal education.